PENGARUH KARAKTERISTIK INDIVIDU DAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KOMITMEN ORGANISASI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA DINAS SYARI’AT ISLAM KABUPATEN ACEH UTARA - Rahmawati Rahmawati; Mariyudi Mariyudi; Ibrahim Qamarius (Universitas Malikussaleh, 2021)
This study examined the effect of individual characteristics and transformational leadership on job satisfaction and organizational commitment of the employees at the Department of Islamic Shari'a. The samples were 114 employees. The analytical tool used was Structural Equation Modeling (SEM) using AMOS (Analysis of Moment Structure) tools. The results showed that individual characteristics and transformational leadership affected job satisfaction. Individual characteristics and job satisfaction also significantly affected organizational commitment. However, transformational leadership did not influence organizational commitment. Then, in testing the indirect relationship, job satisfaction did not mediate the effect of transformational leadership on organizational commitment. But job satisfaction fully mediated the effect of individual characteristics on organizational commitment